Personality in Bonobos. (September 2015) - Weiss, Alexander; Staes, Nicky; Pereboom, Jeffrey J. M.; Inoue-Murayama, Miho; Stevens, Jeroen M. G.; Eens, Marcel
To better understand human and chimpanzee personality evolution, we obtained trait ratings of personality for 154 captive bonobos ( 80% of the U.S. and European population). We found factors that we labeled Assertiveness, Conscientiousness, Openness, Agreeableness, Attentiveness, and Extraversion. The interrater reliabilities and test-retest reliabilities for these factors were comparable to those found in humans and other species. Using orthogonal targeted Procrustes rotations, we compared the bonobo dimensions with those of three samples of captive chimpanzees. Overall congruence coefficients indicated a fair degree of similarity; at the factor level, there was good evidence for Assertiveness, Conscientiousness, Openness, and Agreeableness in the chimpanzee samples; evidence for Attentiveness and Extraversion was poor. These findings suggest that, as expected given their close phylogenetic relationship, bonobo personality structure resembles chimpanzee personality structure in some respects. However, divergent evolution, perhaps as a result of socioecological differences between bonobos and chimpanzees, also appears to have shaped personality structure in these species.